THE SCHOLARSHIP OF ENGAGEMENT AND UNIVERSITY EXTENSION AT THE UNIVERSITY OF ALBERTA - Campbell, Katy (Revista Brasileira de Extensão Universitária, 2017)
Katy Campbell tells us the meaning of ‘engagement scholarship’ in her context and discusses the university extension roles at the University of Alberta. DOI: https://doi.org/10.24317/2358-0399.2017v8i1.4993